Estudio de pertinencia para la creación de una revista impresa, para la difusión turística de la parroquia Chuquiribamba del cantón Loja - Medina Diaz, Rosa Piedad (2017)
The present research analyzes the feasibility of creating a printed magazine for the tourist diffusion of the Chuquiribamba parish, in which it will be able to compile its history, culture, customs, traditions, tourist places, religious festivals and works carried out by the GAD Parish, will highlight the tourism of the parish, with the sole objective that the magazine is a means of communication and information of the sector. The same one that will approach subjects of its history, customs and traditions, places to visit, architecture, gastronomy and its religious festivities, because they are the ones that call the national and foreign tourists. The techniques used in the research were the survey and the interview, the surveys applied to the residents of the sector and the tourists, the interview to the president of the Parish Board. The research project is concluded with the presentation of the proposal for the creation of the magazine, which will inform the population of the sector and also the tourists about the benefits in this field, as well as to encourage tourism through information Timely and adequate.